EVALUASI KEPUASAN PENGUNJUNG TERHADAP REVITALISASI TAMAN ALUN-ALUN TUGU SEBAGAI RUANG TERBUKA HIJAU DI KOTA MALANG - Budiyono (SINTA ID : 6185108), Debora; Kurniawan, Hendra (Universitas Tribhuwana Tunggadewi, 2024)
Malang City Tugu Square Park as a Green Open Space that functions for the ecological urban landscape so as to provide comfort, beauty, and welfare for the city community. Tugu Square Park was revitalized by the Malang City Government in 2023. Changes in the new design of Tugu Square Park caused various reactions from historians, cultural experts, the Association of Landscape Architecture Organizations, and academics because Tugu Square Park is a cultural heritage and is not in harmony with the Malang City Hall building. The purpose of the study was to evaluate visitor satisfaction with the revitalization of Tugu Square Park as a Green Open Space in Malang City. The study method used is descriptive quantitative to determine visitor perceptions of comfort and perceptions of Landscape Architecture students on the visual beauty of the landscape of Malang City's Tugu Square Park. The results of the evaluation of visitor satisfaction with the revitalization of Tugu Square Park as a Green Open Space in Malang City have a satisfied category.